Optical fiber communications : principles and applications - Singal, Tarsem Lal (India : Cambridge University Press, 2016)
"Discusses several dispersion-management schemes that restore amplified signal to its original state"--
Includes bibliographical references (pages 441-443) and index.
Keywords: LCSH:Optical fiber communication